Environmental Determinants Influencing Seasonal Variations of Bird Diversity and Abundance in Wetlands, Northern Region (Ghana) - Nsor, Collins Ayine; Obodai, Edward Adzesiwor (International Journal of Zoology, 2014)
The study assessed major environmental determinants influencing bird community in six wetlands over a 2-year period. A combination of visual and bird sounding techniques was used to determine the seasonal variations in bird abundance, while ordination techniques were performed to determine the influence of environmental factors on bird assemblage. A total of 1,169 birds from 25 species and 885 individuals from 23 species were identified in the wet and dry season, respectively. The shallow close marshes supported the greatest number of birds (P<0.05) compared to the riparian wetlands. Bird diversity was significantly higher in the wet season than in the dry season (F=4.101,P<0.05). Cattle egret (Bubulcus ibis) and marsh warbler (Acrocephalus palustris) were the most abundant. Using the IUCN “Red List” database guide, we noted that 96.2% of birds identified were least concern (LC). The yellow weaver bird (Ploceous megarhrynchus) was the only vulnerable species (VU) and represented 3.8%. From the three variables tested, bushfire and farming practices were the major threats and cumulatively explained 15.93% (wet season) and 14.06% (dry season) variations in bird diversity and abundance. These findings will help wetland managers design conservation measures to check current threats on birds from becoming vulnerable in the future.